2021
DOI: 10.3390/en14154555
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Meteorological Observations over the Island of Ireland to Enhance the Understanding and Prediction of Rain Erosion in Wind Turbine Blades

Abstract: Leading edge erosion is becoming increasingly important as wind turbine size and rainfall are predicted to increase. Understanding environmental conditions is key for laboratory testing, maintenance schedules and lifetime estimations to be improved, which in turn could reduce costs. This paper uses weather data in conjunction with a rain texture model and wind turbine RPM curve to predict and characterise rain erosion conditions across Ireland during rainfall events in terms of droplet size, temperature, humid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In warm and arid climates, sand and dust may be a common type of airborne particulate and therefore may pose leading edge erosion problems, whereas in wetter, greener habitats, the problem may be non-existent. Likewise, at near-shore locations, the issue of sand erosion may be a considerable threat [56][57][58][59]. Leading edge erosion can be a result of rain, with the raindrops' kinetic energy, diameter, temperature and sea salt content being critical parameters [56].…”
Section: Leading Edge Erosionmentioning
confidence: 99%
See 1 more Smart Citation
“…In warm and arid climates, sand and dust may be a common type of airborne particulate and therefore may pose leading edge erosion problems, whereas in wetter, greener habitats, the problem may be non-existent. Likewise, at near-shore locations, the issue of sand erosion may be a considerable threat [56][57][58][59]. Leading edge erosion can be a result of rain, with the raindrops' kinetic energy, diameter, temperature and sea salt content being critical parameters [56].…”
Section: Leading Edge Erosionmentioning
confidence: 99%
“…Likewise, at near-shore locations, the issue of sand erosion may be a considerable threat [56][57][58][59]. Leading edge erosion can be a result of rain, with the raindrops' kinetic energy, diameter, temperature and sea salt content being critical parameters [56]. It has been also observed that careful handling of the blade during manufacturing, transport and installation is essential to avoid small tears or scratches that may act as initiation sites for further wear and erosion [60].…”
Section: Leading Edge Erosionmentioning
confidence: 99%
“…The meteorological data are used to predict erosion behavior based on the Springer model. It has been shown that offshore locations have more severe rain conditions than inland locations in several areas, such as Denmark [ 20 , 21 ], the British Isles [ 22 , 23 , 24 ] and Netherlands [ 25 ]. In the USA, inland conditions vary heavily, as measured by a radar [ 26 ], yet they have a significant effect on leading edge lifetime.…”
Section: Introductionmentioning
confidence: 99%